jtgg 2021
DOI: 10.20517/jtgg.2021.04
|View full text |Cite
|
Sign up to set email alerts
|

The (epi)genomic landscape of splenic marginal zone lymphoma, biological implications, clinical utility, and future questions

Abstract: Splenic marginal zone lymphoma (SMZL) is an indolent B-cell lymphoma comprising less than 2% of lymphoid neoplasms. Approximately 70% of patients have a progressive disease requiring treatment and up to 30% of patients relapse or transform to diffuse large B-cell lymphoma. Whilst research over the last decade has transformed our understanding of many B-cell tumours, it is only beginning to shed light on the molecular pathogenesis of SMZL. Expansive immunogenetic investigations have shown biases in the immunogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…The KLF2 protein comprises activating and inhibitory domains, two nuclear localisation sequences (NLSs), and three zinc finger motifs (ZnFs). KLF2 mutations are present in 20-40% of SMZL cases [60,61] and in three studies were also found in 9/74 (12%) cases of HCLc cases [42,62,63]. Mutations may occur in the activation, inhibitory, zinc finger or nuclear localisation domains, are predominantly truncating or missense, and reduce the transcriptional activity of KLF2, partly by displacement from the nucleus if mutations involve the NLS (Figure 4).…”
Section: • Klf2mentioning
confidence: 92%
“…The KLF2 protein comprises activating and inhibitory domains, two nuclear localisation sequences (NLSs), and three zinc finger motifs (ZnFs). KLF2 mutations are present in 20-40% of SMZL cases [60,61] and in three studies were also found in 9/74 (12%) cases of HCLc cases [42,62,63]. Mutations may occur in the activation, inhibitory, zinc finger or nuclear localisation domains, are predominantly truncating or missense, and reduce the transcriptional activity of KLF2, partly by displacement from the nucleus if mutations involve the NLS (Figure 4).…”
Section: • Klf2mentioning
confidence: 92%
“…Mutations of negative regulators of NOTCH signaling (such as SPEN, DTX1, and MAML2) can also be seen, reinforcing the importance of this signaling pathway [13]. Moreover, NOTCH2 mutations are associated with reduced treatment-free survival [57,58].…”
Section: Mutational Landscapementioning
confidence: 97%
“…Mutations of P53, involved in cell cycle control, are described in 15% of cases and predominate at the DNA-binding domain [48]. These mutations seem to be associated with short overall survival [29,58,61]. In the study of Clipson et al, MYD88 and TP53 mutations are exclusively found in patients lacking KLF2 mutations.…”
Section: Mutational Landscapementioning
confidence: 99%
“…1 , 2 , 3 Compared with other B-cell lymphomas, SMZL is characterized by few recurrent chromosomal abnormalities, including deletions of 7q31-q32 (30% to 40%) and 6q (8% to 24%), and gains of chromosomes 3/3q (20% to 30%) and 18/18q (8% to 25%). 4 , 5 , 6 , 7 , 8 The most frequent mutations in SMZL include KLF2 (20% to 30%), NOTCH2 (10% to 25%), TP53 (15%), KMT2D (10% to 15%), and TNFAIP3 (7% to 15%). 9 , 10 , 11 , 12 , 13 Recently, Bonfiglio et al 14 reported a large comprehensive genomic and transcriptomic characterization of 303 SMZLs at diagnosis, dividing SMZL into 2 main genetic clusters: (1) DMT cluster characterized by alterations in DNA-damage response and mitogen-activated protein kinase, and Toll-like receptor pathways (∼30% of SMZL); and (2) NNK cluster, characterized by alterations on nuclear factor κB (NF-κB), NOTCH2 , and KLF2 (∼60% of SMZL), and associated with an inferior survival.…”
Section: Introductionmentioning
confidence: 99%